THU0382 ARTICULAR MANIFESTATIONS IN PATIENTS WITH INFLAMMATORY BOWEL DISEASES TREATED WITH ANTI-TNFΑ. (2nd June 2020) - Cachen, L.; Nocturne, G.; Collins, M.; Meyer, A.; Carbonnel, F.; Mariette, X.; Seror, R.
Abstract : Background: Articular manifestations are the most frequent extra-digestive manifestations of Inflammatory Bowel Disease (IBD). Anti-TNF have proved to be as effective on articular symptoms as on IBD's ones, but have been suspected to induce paradoxical articular manifestations. Objectives: The aims of this study were to describe the frequency, the type and the management of all articular manifestations occurring in patients treated with anti-TNF for IBD and to look for factors associated with their occurrence. Methods: In this retrospective monocentric study, we included all patients who received an anti-TNF for an IBD in our tertiary hospital referent for inflammatory rheumatic and bowel diseases. We searched for all incident articular manifestations occurring during treatment with anti-TNF, including new or recurrent articular manifestations. Characteristics of patients with paradoxical articular manifestations (defined as inflammatory articular symptoms occurring while IBD was in remission, without immunization against anti-TNF) were compared to that of patients without articular manifestations to identify factors associated with their occurrence. Results: Through a systematic search of all IBD patients seen in our tertiary hospital between February 2013 and May 2017, we identified 442 patients (36.2±15 years, 50.5% men) who had ever received an anti-TNF for IBD: Crohn's disease (n=277), ulcerative colitis (154) and undetermined colitis (n=11). 74 (16.7%) had already a history of inflammatory articular manifestations including 37 patients with a diagnosis of spondyloarthritis (SpA) made before anti-TNF's beginning. Among them, 115 (26%) patients developed a new articular manifestation after a mean of 20 (±22) months of treatment: mechanical in 56 (12.6%) and inflammatory in 59 (13.3%). Within patients with new inflammatory articular manifestations: 39% were paradoxical, 27% were concomitant of an IBD flare, 27% were associated to an immunization against anti-TNF, 3% were induced lupus, 2% were chondrocalcinosis and 2% were polymyalgia rheumatic. Articular manifestations associated to an immunization were linked to a loss of efficiency of the treatment for 62%, with (42%) or without (20%) associated digestive symptoms and 38% were due to delayed hypersensitivity reaction. Among paradoxical articular manifestations, 83% were new articular symptoms, including 35% of SpA de novo, and 17% were recurrence of known articular manifestations. The only predictive factor of paradoxical articular manifestation was a previous diagnosis of SpA (21.7% vs 6.8%; p=0.02). Paradoxical manifestations improved in 17 patients despite continuation of anti-TNF, methotrexate was added in 2 and anti-TNF was discontinued in only 4 patients. Conclusion: Inflammatory articular manifestations occurred in about 13% of patients treated with anti-TNF for IBD. More than a quarter were linked to an immunization against anti-TNF, which has to be searched in this situation. Less than half of them (39%) were paradoxical. In most of cases, they were transitory and did not require anti-TNF's discontinuation. The only predictive factor of paradoxical articular manifestations was having a history of SpA. References: [1]Thiebault H, et al. Paradoxical articular manifestations in patients with inflammatory bowel diseases treated with infliximab. Eur J Gastroenterol Hepatol, 2016. [2]Fiorino G et al. Paradoxical immune-mediated inflammation in inflammatory bowel disease patients receiving anti-TNF-α agents. Autoimmun Rev, 2014. Disclosure of Interests: Laurie Cachen: None declared, Gaetane Nocturne: None declared, Michael Collins Consultant of: Abbvie, Takeda, MSD, Celgene, Antoine Meyer: None declared, Franck Carbonnel Consultant of: Msd Abbvie Amgen, Xavier Mariette Consultant of: BMS, Gilead, Medimmune, Novartis, Pfizer, Servier, UCB, Raphaèle Seror Consultant of: BMS UCB Pfizer Roche